Composition of cassava - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
The chemical composition and corresponding value of cassava in the South Pacific is better understood as a result of research being carried out in the region. The Australian National University (ANU), supported by the Australian Centre for...